Postabortion and safe abortion care coverage, capacity, and caseloads during the global gag rule policy period in Ethiopia and Uganda - Melissa Stillman; Simon P. S. Kibira; Solomon Shiferaw; Fredrick Makumbi; Assefa Seme; Elizabeth A. Sully; Lilian Ha; Margaret Giorgio (BMC, 2023)
Abstract Background Abortion-related complications contribute to preventable maternal mortality, accounting for 9.8% of maternal deaths globally, and 15.6% in sub-Saharan Africa. High-quality postabortion care (PAC) can mitigate the negative health outcomes associated with unsafe abortion. While the expanded Global Gag Rule policy did not prohibit the provision of PAC, other research has suggested that over-implementation of the policy has resulted in impacts on these services. The purpose of this study was to assess health facilities' capacity to provide PAC services in Uganda and PAC and safe abortion care (SAC) in Ethiopia during the time in which the policy was in effect. Methods We collected abortion care data between 2018 and 2020 from public health facilities in Ethiopia (N = 282) and Uganda (N = 223). We adapted a signal functions approach to create composite indicators of health facilities' capacity to provide basic and comprehensive PAC and SAC and present descriptive statistics documenting the state of service provision both before and after the GGR went into effect. We also investigate trends in caseloads over the time-period. Results In both countries, service coverage was high and improved over time, but facilities' capacity to provide basic PAC services was low in Uganda (17.8% in 2019) and Ethiopia (15.0% in 2020). The number of PAC cases increased by 15.5% over time in Uganda and decreased by 7% in Ethiopia. Basic SAC capacity increased substantially in Ethiopia from 66.7 to 82.8% overall, due in part to an increase in the provision of medication abortion, and the number of safe abortions increased in Ethiopia by 9.7%. Conclusions The findings from this analysis suggest that public health systems in both Ethiopia and Uganda were able to maintain essential PAC/SAC services during the GGR period. In Ethiopia, there were improvements in the availability of safe abortion services and an overall improvement in the safety of abortion during this time-period. Despite loss of partnerships and potential disruptions in referral chains, lower-level facilities were able to expand their capacity to provide PAC services. However, PAC caseloads increased in Uganda which could indicate that, as hypothesized, abortion became more stigmatized, less accessible and less safe.